PENGARUH PREMI ASURANSI, PERSEPSI RISIKO, PENDAPAT DAN JUMLAH TANGGUNGAN TERHADAP MINAT MEMILIH ASURANSI KESEHATAN - Inayah, Mia Inayah; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 11 (2024): Vol.13.No.11. NOVEMBER 2024 [765-830]DO - 10.24843/EEP.2024.v13.i11.p01, 2025)
Insurance is an effort made by many parties as an attempt to protect lives and other valuable goods from an uncertainty and risk that causes losses in the future. The insurance industry plays a key role in facing risks and has a significant contribution in maintaining economic stability and the financial system. Therefore, this study aims to analyze the effect of insurance premiums, risk perception, income and number of dependents on the interest in having health insurance, both simultaneously and partially on BPJS insurance and private insurance. This study uses descriptive quantitative methods with the analysis technique used is binary logistic regression analysis. Based on the results of this study, insurance premiums, risk perception and income prefer to have private insurance compared to BPJS Health insurance. While the number of dependents has a negative effect on the interest in having BPJS health insurance, because the more the number of dependents, the more interested to have BPJS health insurance compared to private insurance. Keywords : insurance, risk perception, insurance premium, number of dependents, income